Forage accumulation and nutritive value of the Urochloa interspecific hybrid ’BRS RB331 Ipyporã’ under intermittent grazing - Echeverria, Joilson Roda; Euclides, Valéria Pacheco Batista; Sbrissia, Andre Fischer; Montagner, Denise Baptaglin; Barbosa, Rodrigo Amorim; Nantes, Nayana Nazareth (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the forage accumulation and nutritional value of the Urochloa hybrid 'BRS RB331 Ipyporã' (Urochloa brizantha x Urochloa ruziziensis) subjected to intermittent grazing. The treatments corresponded to combinations of the pre‑grazing conditions, interception of 95% of incident light and maximum light interception, and of the post‑grazing heights, 10 and 15 cm, in a randomized complete block design with a 2x2 factorial arrangement and four replicates. Pastures grazed at 95% of light interception showed higher forage accumulation rate, proportion of leaves, leaf:stem ratio, crude protein content, and basal tiller population density (BTPD), in comparison with those managed at maximum light interception. Pastures managed with post‑grazing heights of 15 cm showed greater BTPD than those managed at 10 cm and showed a slightly variation in BTPD among the evaluated seasons of the year, regardless of the treatment. Pastures of the interspecific hybrid of Urochloa 'BRS RB331 Ipyporã' show greater forage accumulation and higher crude protein content and in vitro organic matter digestibility, and lower content of neutral detergent fiber in the leaf fraction, when managed with 95% LI under pre‑grazing conditions of 30-cm sward height, associated with a post‑grazing 15-cm sward height.